Pengaruh Keterbatasan Fasilitas Pembelajaran Terhadap Prestasi Belajar Siswa SMP Negeri 5 Katingan Tengah - yanti, Indri Dama; Setiawati, Nani; Yedithia, Fenroy (Journal Of Dehasen Educational Review, 2025)
Educational infrastructure functions as a pivotal catalyst underpinning the pedagogical dynamic within schools. The sufficiency of such resources not only amplifies learner engagement and comprehension but also elevates the holistic quality of education. This investigation seeks to elucidate how deficiencies in learning amenities influence academic achievement at SMP Negeri 5 Katingan Tengah, an institution currently grappling with inadequate computer labs, scientific apparatus, sports equipment, and internet access. Consequently, students confront challenges in grasping subject matter, relying predominantly on textual content and oral instruction absent of enriching visual aids or hands-on practicum. Employing a descriptive qualitative framework through observations and student interviews, findings reveal that tangible, interactive educational media substantively enhance material comprehension and stimulate active learner participation. Accordingly, the provision of comprehensive educational facilities emerges as indispensable for fostering effective and high-caliber learning environments. It is imperative that local authorities prioritize the augmentation of school infrastructure, particularly in under-resourced institutions such as SMP Negeri 5 Katingan Tengah.